Bioaugmented constructed wetlands for denitrification of saline wastewater: A boost for both microorganisms and plants. (May 2020) - Wang, Xinyi; Zhu, Hui; Yan, Baixing; Shutes, Brian; Bañuelos, Gary; Wen, Huiyang
Graphical abstract: Highlights: Bioaugmentation improved nitrogen removal in CWs under salt stress. Salt-tolerant microbial inoculum promoted the growth of wetland plants. The abundance of salt-tolerant microorganisms increased in Bio-CWs. Bioaugmentation boosted the function of both microorganisms and plants in CWs. Abstract: The inhibition of salt stress on plant and microbial functions has led to the reduction of nitrogen removal capacity of constructed wetlands (CWs) under saline conditions. The mechanisms and effectiveness of bioaugmented CW (Bio-CW) microcosms with a salt-tolerant microbial inoculum were evaluated for nitrogen removal at different salinity levels. The results showed that the denitrification capacity of CWs was improved under saline conditions by adding the salt-tolerant microbial inoculum. At an EC of 15 mS/cm, the removal percentages of ammonia nitrogen (NH4 + -N) and total nitrogen (TN) in Bio-CW microcosms (95.7% and 99.4%) on Day 5 were significantly ( p  < 0.05) higher than that in unbioaugmented CW (un-Bio-CW) microcosms (68.5% and 76.4%), respectively. The high throughput sequencing data of substrate samples indicated that the microbial community in the CWs was changed by the addition of the salt-tolerant microbial inoculum and the frequency of bacteria with nitrogen removal function was increased in the CWs. Furthermore, both growth and the TN accumulation capacity of plants in Bio-CW microcosms were promoted compared with the un-Bio-CW microcosms. In conclusion, the addition of the salt-tolerant microbial inoculum can enhance the nitrogen removal efficiency of CWs under saline condition via boosting the function of both microorganisms and plants.